A new era in Sport Organizations and coach development in Finland - Hämäläinen, K.; Blomqvist, M. (International Sport Coaching Journal, 2016)
The purpose of this article is to describe recent actions for sport organizations and coach development in Finland. Finnish Sport organizations and systems especially in high-performance sports have been in a transition phase in recent years. The high-performance sport systems have been analyzed and reorganized and new strategic goals were set. Coach development was chosen as one of the focus areas and the leadership of coach development is at the new High Performance Unit of the Olympic Committee. There are different education paths for coaches and all the organizations which provide coach education belong to a network for coach development. This network works for developing programs, learning concepts and tools and sharing of expertise. One key idea of the development work has been to conduct systematic research among Finnish coaches to gain objective information of coaches` needs and learning experiences. As a result of this work, the Finnish Coach Competence Model was created as a tool and for creating common understanding of coaches` competences and for developing education programs and coaches` assessment. Creating a new learning culture and a network have been the main steps so far and the further development for those are also the main goals in future.